Spatiotemporal Characteristics of Reservoir-Induced Earthquakes Using P-Wave Velocity Structures - Zhiren Feng; Bo Jin; Hongfu Lei; Di Liu (Shock and Vibration)
In this study, through the seismic phase observation report obtained by a river reservoir seismic network from September 2012 to July 2015, the joint inversion method of source and velocity structure is employed, combined with the regional seismic geological environment data. Such method gives the P-wave velocity structure of different sections in the reservoir area and tries to find out the impact range of the reservoir water depth. And the impact of reservoir water infiltration on crustal medium is discussed. The obtained location results show that the earthquake activity is mainly concentrated in the first reservoir tail and the second reservoir head. As such, the spatial distribution characteristics of the recorded earthquakes are given, and the resolution results of detection board at different depths are speculated and discussed.